2014
DOI: 10.1007/978-3-642-54830-7_10
|View full text |Cite
|
Sign up to set email alerts
|

Unsafe Order-2 Tree Languages Are Context-Sensitive

Abstract: Abstract. Higher-order grammars have been extensively studied in 1980's and interests in them have revived recently in the context of higher-order model checking and program verification, where higher-order grammars are used as models of higher-order functional programs. A lot of theoretical questions remain open, however, for unsafe higher-order grammars (grammars without the so-called safety condition). In this paper, we show that any tree languages generated by order-2 unsafe grammars are context-sensitive.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, the languages of the oi-hierarchy are generated by so-called "safe" high-level grammars, and it is not known whether the same results hold for unsafe high-level grammars. It is proved in [54] that the languages generated by unsafe level-2 grammars, the unsafe version of OI (2), are in NSPACE(n).…”
Section: Resultsmentioning
confidence: 99%
“…However, the languages of the oi-hierarchy are generated by so-called "safe" high-level grammars, and it is not known whether the same results hold for unsafe high-level grammars. It is proved in [54] that the languages generated by unsafe level-2 grammars, the unsafe version of OI (2), are in NSPACE(n).…”
Section: Resultsmentioning
confidence: 99%
“…A problem still open is whether languages defined by such grammars are context sensitive, or in other words if they belong to the complexity class NLINSPACE (non-deterministic linear space). Recent progresses on this problem have been achieved by Kobayashi et al [17], who showed that this is at least the case up to order 2 for tree languages and order 3 for word languages. Beside the fact that this line of research does not target a capturing result, the most significant difference with our work is that we consider a polyadic μ-calculus, or in different words, an automaton model that uses multiple tapes, whereas collapsible pushdown automata (the automaton model for higher-order grammars) only work with one tape.…”
Section: Contributionsmentioning
confidence: 99%
“…Intersection type systems were intensively used in the context of recursion schemes, for several purposes like model-checking [18,21,5,29], pumping [19,2], transformations of HORSes [20,1,8], etc. Interestingly, constructions very similar to intersection types were used also on the side of collapsible pushdown systems; they were alternating stack automata [4], and types of stacks [23,16].…”
Section: Introductionmentioning
confidence: 99%